Exploring the role of technology innovation and environmental regulation in energy efficiency - Chen, Yushan; Zhao, Tong (Frontiers in Environmental Science, 2022)
This paper adopts a relatively infrequent approach to explore the impact of environmental regulation and technological innovation on energy efficiency (hereinafter referred to as EFF) , based on the undesired super-efficiency SBM and random Tobit model. In order to study the universal EFF, we establish the undesired super-efficiency SBM model, which is composed of three input indexes such as energy, one expected output index, three pollution emissions as the undesired output index, and consider the EFF of the sample with effective decision making unit value less than 1, and calculate with the Matlab software，according to panel data of 30 Chinese provincial-level regions from 2001 to 2019. The empirical results show that the EFF has an N-type trend in the eastern, central and western regions in China. When exploring the impact of environmental regulation and technological innovation on EFF, we conduct empirical analysis of the eastern, central and western regions with the random Tobit model. The regression results indicate that: the impact of environmental regulation on EFF in the different regions varies significantly. Technological innovation has different impacts on EFF in different regions, and it is also the main influencing factor of EFF. Moreover, we strive to analyze the impact of cross term environmental regulation and technological innovation, and find that the cross term has a significant positive impact on EFF in each region. These results emphasize that environmental regulation and technological innovation have positive or negative impacts on EFF, and even both impacts may exist at the same time, which is a perfection of the EFF theory.